Heterogeneous labour markets in a microsimulation-AGE model: application to welfare reform in Germany - Stefan Boeters; Michael Feil (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Labour market reforms that are designed to stimulate labour supply at the lower end of the wage distribution can never be precisely restricted to affect only the target group. Spillovers to and feedback from other segments of the labour market are unavoidable and may counteract the direct effects of the reform. An adequate representation of heterogeneous labour markets becomes therefore an important issue for the assessment of reforms. We analyse the possible interactions between labour market segments in a combined, consistent microsimulation-AGE model with a flexible representation of substitution possibilities and different wage-forming regimes. We look at a stylised reform and find labour-demand cross-price elasticities between the low and medium skilled to be the main drivers of the results. Interaction with the high-skilled segment is less pronounced.
Older version: http://hdl.handle.net/10419/24739
Keywords: D58; J22; J51; 330; Applied general equilibrium model; microsimulation; discrete working time choice; heterogeneous labour markets; labour market reform; Hartz-Reform; Wirtschaftspolitische Wirkungsanalyse; Arbeitsangebot; Ökonomischer Anreiz; Arbeitsmarktsegmentierung; Qualifikation; Lohnverhandlungen; Mikrosimulation; Allgemeines Gleichgewicht; Theorie; Deutschland